The d-Enantiomer Form of Indobufen Totally Accounts for the Anti-Cyclooxygenase and Antiplatelet Activity Ex Vivo and for the Increase in Bleeding Time by Indobufen in Man - Caterina, Raffaele De; Sicari, Rosa; Yan, An; Bernini, Walter; Giannessi, Daniela; Lazzerini, Guido; Efthymiopoulos, Costantin; Strolin-Benedetti, Margherita (Thrombosis and Haemostasis, 1992)
Indobufen is an antiplatelet drug able to inhibit thromboxane production and cyclooxygenase-dependent platelet aggregation by a reversible inhibition of cyclooxygenase. Indobufen exists in two enantiomeric forms, of which only d-indobufen is active in vitro in inhibiting cyclooxygenase. In order to verify that also inhibition of platelet function is totally accounted for by d-indobufen, ten patients with proven coronary artery disease (8 male, 2 female, age, mean ± S.D., 58.7 ± 7.5 years) were given, in random sequence, both 100 mg d-indobufen and 200 mg dl-indobufen as single administrations in a double-blind crossover design study with a washout period between treatments of 72 h. In all patients thromboxane (TX) B2 generation after spontaneous clotting (at 0, 1, 2, 4, 6, 8, 12, 24 h), drug plasma levels (at the same times), platelet aggregation in response to ADP, adrenaline, arachidonic acid, collagen, PAF, and bleeding time (at 0, 2, 12 h) were evaluated after each treatment. Both treatments determined peak inhibition of TXB2 production at 2 h from administration, with no statistical difference between the two treatments (97 ±3% for both treatments). At 12 h inhibition was 87 ± 6% for d-indobufen and 88 ± 6% for dl-indobufen (p = NS). Inhibition of TXB2 production correlated significantly with plasma levels of the drugs. Maximum inhibitory effect on aggregation was seen in response to collagen 1.5 pg/ml (63 ± 44% for d-indobufen and 81 ± 22% for dl-indobufen) and arachidonic acid 0.5-2 mM (78 ± 34% for d-indobufen and 88 ± 24% for dl-indobufen) at 2 h after each administration. An effect of both treatments on platelet aggregation after 12 h was present only for adrenaline 2 μM (55 ± 41% for d-indobufen and 37 ± 54% for dl-indobufen), collagen 1.5 pg/ml (69 ± 30% for d-indobufen and 51 ± 61% for dl-indobufen), arachidonic acid 0.5-2 mM (56 ± 48% for d-indobufen and 35 ± 49% for dl-indobufen). The extent of inhibition of TX production and the extent of residual platelet aggregation were never significantly different between treatments. Bleeding time prolongation was similar in the two treatment groups without showing a pronounced and long lasting effect (from 7.0 ± 2.0 min to 10.0 ± 3.0 min at 2 h and 8.0 ± 2.0 min at 12 h for d-indobufen; from 6.0 ±1.0 min to 8.5 ± 2.0 min at 2 h and 8.0 ± 1.0 min at 12 h for dl-indobufen). These results demonstrate that the biological activity of dl-indobufen as an antiplatelet agent in vivo is totally accounted for by d-indobufen.